The impact of hospital competition on healthcare quality: evidence from China’s healthcare reform - Huimin Liu; Junyan Jiang; Liangchun Yu; Xianpeng Liu (Frontiers in Public Health)
IntroductionHospital competition has been a common feature in healthcare reforms worldwide, yet scant attention has been paid to its impact on healthcare quality in China. This study aims to comprehensively evaluate the impact of hospital competition on healthcare quality under China’s healthcare reform.MethodsThis study used multiple datasets comprising city-level and individual-level data of 21,974 individuals across 150 districts. We employed a two-way fixed effects model to estimate the impact of hospital competition on healthcare quality. To mitigate endogeneity concerns, we instrumented hospital competition with the inverse of the average distance and average travel time from patients to hospitals and performed the Two-Stage Least Squares methods.ResultsThis study showed a positive effect of hospital competition on both technical and non-technical healthcare quality. The impact is larger for primary hospitals and inpatient services; it is significantly positive for technical healthcare quality in public hospitals. Additionally, our findings implied that hospital competition affects healthcare income, which in turn affects non-technical healthcare quality, but healthcare income and demand jointly influence the relationship between hospital competition and technical healthcare quality.ConclusionThe finding provides new evidence of the impact of hospital competition on both technical and non-technical healthcare quality in China, highlighting a positive relationship that differs from some previous studies. This evidence offers valuable policy implications on hospital competition and also emphasizes the importance of considering the heterogeneity of hospitals and services in policy-making.